Frequency of Hypothyroidism in Children of Celiac Disease - Khalid, Qurat Ul Ain (International Journal of Pathology, 2020)
Background: Hypothyroidism is a rare finding in children having celiac disease but it has severe effects on mental & physical health of children.Objective: To assess the frequency of hypothyroidism in children diagnosed with celiac disease.Methods: This cross sectional study was conducted at Department of Pediatrics, Military Hospital and Dr. Akbar Niazi Teaching hospital, Bhara Kahu. 60 consecutive children having celiac disease (positive anti-TTG and endoscopy) were included in the study. Thyroid function tests were done to assess thyroid function. TSH ≥5mIU/L with T4<7.5µg/L as hypothyroidism. Data was a recorded on proforma and analyzed through SPSS v. 21.0.Results: The mean age of children was 6.57±2.18years. There were 20 (33.3%) males and 40 (66.7%) females. Out of 60, hypothyroidism was detected in 2 (3.3%) cases.Conclusion: Hypothyroidism is present in only very few children with celiac diseases. But children with celiac disease should be screened for hypothyroidism, as they may be asymptomatic and can have hazardous consequences.